Review of Cyber Security on Oil and Gas Industry in United Arab Emirates: Analysis on the Effectiveness of the National Institute of Standards and Technology’s (NIST) Cybersecurity Framework - et. al., Mohamed Jumah ALDhanhani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In view of increasing cyber attacks, the adoption of an effective security framework is essential for any organization involved in critical sectors, such as the oil and gas sector, to ensure the highest level of security and compliance. In this regard, as one of the major oil producers and exporters, the United Arab Emirates (UAE) needs to employ an effective security framework to protect the critical infrastructures of its oil and gas sector. As such, this study iscarried out to examine the potential harms of cyber attacks by focusing on the elements of the cybersecurity framework of the National Institute of Standards and Technology. The research methodology used in this research is based on a systematic review of the current literature on cyber security and frameworks. The review revealsthat NIST’s cybersecurity framework has certain features that apparently make it more effective than others. Essentially, this framework has three main components, namely the framework core, implementation tiers, and profile, which are defined based on an organization’s business. Specifically, the framework core has five functions, namely identify, protect, detect, respond, and recover. The findings of this research can help guide policy makers in the UAE’s oil and gas industry to make informed decisions on how to best mitigate cyber threats against oil companies. In particular, the findings can assist policy makers to determine whether the NIST’s cybersecurity framework can play an essential role in strengthening cyber security in the UAE's oil and gas sector. Moreover, the findings can help practitioners to recommend appropriate practical measures to strengthen the preparedness and responses of oil and gas companies in the UAE to cyber attacks.